2011
DOI: 10.1017/s0033291711000742
|View full text |Cite
|
Sign up to set email alerts
|

Is obsessive–compulsive disorder an anxiety disorder, and what, if any, are spectrum conditions? A family study perspective

Abstract: On the basis of co-morbidity and familiality, OCD appears related both to anxiety disorders and to some conditions currently classified in other sections of DSM-IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
114
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(128 citation statements)
references
References 40 publications
14
114
0
Order By: Relevance
“…The strong association between trichotillomania and OCD is also supported by three earlier studies that reported higher prevalence of OCD in first-degree relatives of patients with trichotillomania (compared to the general population) either via collection of family history or direct interviewing of relatives (Lenane et al 1992;Schlosser et al 1994;King et al 1995). More recently, elevated grooming disorders including trichotillomania alone was also reported in OCD probands and their relatives compared to controls (Bienvenu et al 2012). …”
Section: Comorbiditysupporting
confidence: 60%
“…The strong association between trichotillomania and OCD is also supported by three earlier studies that reported higher prevalence of OCD in first-degree relatives of patients with trichotillomania (compared to the general population) either via collection of family history or direct interviewing of relatives (Lenane et al 1992;Schlosser et al 1994;King et al 1995). More recently, elevated grooming disorders including trichotillomania alone was also reported in OCD probands and their relatives compared to controls (Bienvenu et al 2012). …”
Section: Comorbiditysupporting
confidence: 60%
“…Much debate has ensured regarding whether OCD should be considered an anxiety disorder, with overall mixed opinion based upon various categories of validators (Stein et al 2010). The limited data from extant genetic epidemiological studies suggest that OCD does share some familial (Bienvenu et al 2012) and genetic (Tambs et al 2009) risk factors with anxiety disorders, although OCD also shares risk with obsessive-compulsive spectrum disorders (Monzani et al 2014). No studies have included both of these groups to determine if these represent distinct genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Family studies indicate that BDD is more common in firstdegree relatives of OCD probands than control probands, suggesting shared etiology (genetic and/or environmental) with OCD (36)(37)(38). Similarly, a twin study, which can tease apart genetic versus environmental influences, found that "dysmorphic concern" (a concept with similarities to BDD) has shared genetic vulnerability with other obsessive-compulsive and related disorders, including OCD; in addition, the study found BDD-specific genetic influences (heritability of 43%) (39).…”
Section: Genetic Factorsmentioning
confidence: 99%